Experimental evaluation of mechanical properties of friction welded mild steel - Eko Nugroho; Eko Budiyanto; Enggal Bagus Suseno (TURBO [Tulisan Riset Berbasis Online], 2021)
Friction welding is a solid state joining process used to join similar and dissimilar metals, not possible with other available welding techniques. Now a day’s Friction welding is most commonly used in industry that is aeronautical engineering, automobile engineering, submarine industry and heavy industry. In this research, an experimental setup was designed and fabricated in order to accomplish friction welded joints mild steel. Thereafter, the effect of forging pressures and rotation speed on the mechanical properties of friction welded ST 42 steels, produced by mechanical joining, have been investigated. Samples were welded under friction pressure 10 MPa by different forging pressures 25 MPa and 35 MPa with different rotation speed 1095 rpm, 1200 rpm, and 1400 rpm. The tensile strength values of the weldments were determined and evaluated. The top result is produced from sample were welded under forging pressures 35 MPa at rotation speed 1400 rpm that is tensile strength 437,27 N/mm2 and yield strength 399,75 N/mm2.Keywords : friction welding, forging pressure, tensile strength, yield strength, and elongation.